Permainan Tradisional “Pancasila Lima Dasar” untuk Meningkatkan Keterampilan Berbahasa pada Siswa Tunagrahita - Ratri wikaningtyas; Martselani Adias Sabara (Jurnal Yudistira : Publikasi Riset Ilmu Pendidikan dan Bahasa, 2023)
This research was motivated by the lack of language skills and social interaction among students with intellectual disabilities. Apart from that, it is to reintroduce traditional games to millennial generation children. This research is classroom action research with two cycles. From the research results, there was an increase in cycle II. With each average percentage, cycle I got a result of 64.70665 and cycle II got a result of 88.15999.